2007
DOI: 10.1590/s0102-76382007000100007
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo entre o pré-condicionamento isquêmico e a drenagem liquórica como métodos de proteção medular em cães

Abstract: Cerebrospinal fluid drainage and immediate ischemic preconditioning seems to protect the spinal cord during descending thoracic aorta cross-clamping. Nevertheless, the obtained level of spinal cord protection seems to be more significant with cerebrospinal fluid drainage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…lumbar drains opened just before cross clamping) [ Table 2 ]. [ 3 ] At 7 postoperative days, the Tarlov neurological scores were significantly higher for the animals receiving CSFD, and they demonstrated faster/fuller recovery of adverse SEP changes.…”
Section: Methodsmentioning
confidence: 99%
“…lumbar drains opened just before cross clamping) [ Table 2 ]. [ 3 ] At 7 postoperative days, the Tarlov neurological scores were significantly higher for the animals receiving CSFD, and they demonstrated faster/fuller recovery of adverse SEP changes.…”
Section: Methodsmentioning
confidence: 99%
“…Saba et al39 describe the total absence of neuroprotective effects of diltiazem in rabbits with occluded aorta. Neuroprotective effects of diltiazen, Benício et al40 compared ischemic preconditioning and cerebrospinal fluid drainage as methods of spinal cord protection in dogs and found that cerebrospinal fluid drainage and immediate ischemic preconditioning seem to protect the spinal cord during descending thoracic aorta cross-clamping. Nevertheless, spinal cord protection seems to be more significant with cerebrospinal fluid drainage.…”
Section: Neurologymentioning
confidence: 99%